Biodegradation and toxicological evaluation of lubricant oils - Tamada, Ivo Shodji [UNESP]; Lopes, Paulo Renato Matos [UNESP]; Montagnolli, Renato Nallin [UNESP]; Bidoia, Ederio Dino [UNESP] (Brazilian Archives of Biology and Technology, 2012)
The aim of this work was to compare different toxicity levels of lubricant oils. The tests were performed using the earthworm (Eisenia andrei), arugula seeds (Eruca sativa) and lettuce seeds (Lactuca sativa), with three types of contaminants (mineral lubricant oil, synthetic lubricant oil and used lubricant oil) for various biodegradation periods in the soil. The toxicity tests indirectly measured the biodegradation of the contaminants. The samples were analyzed at t0, t60, t120 and t180 days of biodegradation. The used lubricant oil was proved very toxic in all the tests and even after biodegradation its toxicity was high. The mineral and synthetic oils were biodegraded efficiently in the soil although their toxicity did not disappear completely after 180 days.
Keywords: Toxicology; biodegradation; lubricant oil; toxicity bioassay